The Effect of Furrow Containing Organic Matters to Upland Rice (Oryza sativa L.) Growth and Yield in Agroforestry System with Kayu Putih - Puji Lestari Tarigan; Tohari Tohari; Priyono Suryanto (Jurnal Ilmu Pertanian, 2019)
This research was aimed to know the effects of the furrow system containing organic matter for rainfed, to growth and yield of several varieties on agroforestry system with Kayu Putih. The research was conducted in Petak 83 Resort Pengelolaan Hutan (RPH) Menggoran, Bagian Daerah Hutan (BDH) Playen, Kesatuan Pengelolaan Hutan (KPH) Yogyakarta from March to August of 2018. The experimental design applied the strip plot design. The vertical factor was the furrow system of treatment consisting of 2 levels i.e, without furrow + without organic matter and furrow + organic matters. The horizontal factors were the varieties of upland rice consisting of 3 varieties i.e. Situ Patenggang, Situ Bagendit, and Ciherang. Then the collected data were analyzed by analysis of variance (Anova) applying a level of significance α = 5%. Whenever the significant differences among treatments were found, further analysis was carried out by applying the Tukey's HSD (Honestly Significant Difference) at 5% levels. The result showed that furrow containing organic matter was able to support plant growth in dry land. Situ Patenggang has highest adaptation to growth dan produce in drought stress. The combination of furrow containing organic matter with Situ Patenggang showed the best result in CGR, total root length, total chlorophyll content, number of panicle, number of spikelet per panicle, 1000 grain weight and estimated productivity.